Effect of Giving Fermented Liquid Areca Cathecu L. and Surian Leaves (Toona sinensis ROXB.) On Tilapia Wounds (Oreochromis niloticus L.) - Audina Mutia (Universitas Negeri Padang, 2018)
Tilapia (Oreochromis niloticus L.) is a species originating from the Nile River region and surrounding lakes in Africa. Maintenance of tilapia is also at risk for diseases and pests. Diseases in fish require fast and effective handling, namely by administering drugs. The use of safe, environmentally friendly, and low-cost drugs is herbal medicine, which is using areca leaf fermentation liquid (Arecha cathecu L.) and surian leaves (Toona sinensis ROXB.) This research is an experimental study, using a completely randomized design (CRD) consisting from 4 treatments and 6 replications with 7 days of observation. Data were analyzed using Analysis Of Variants (ANOVA), the results were significantly different followed by continued testing of DNMRT level of 5%. Based on the research conducted, it is known that the dosage of Areca cathecu L. and surona sinensis ROXB. Fermented leaves which has the most effect on wound healing in tilapia (Oreochromis niloticus L.) which has the longest wound healing is 0.54 cm in A3 treatment (administration of areca leaf fermented liquid and surian leaves with a dose of 15 ml while the lowest healing was at 0 ml (control).